+0  
 
0
42
1
avatar

Let $a$ and $b$ with $a>b>0$ be real numbers satisfying $a^2+b^2=4ab$. Find $\dfrac{\sqrt{a}}{\sqrt{b}} - \dfrac{\sqrt{b}}{\sqrt{a}}$.

 Feb 5, 2021
 #1
avatar+116049 
+1

sqrt a  / sqrt b  -    sqrt b  /  sqrt  a   =

 

(sqrt a)^2   -  (sqrt b)^2                a   -   b

___________________   =        _______       (1)

     sqrt (ab)                                 sqrt  (ab)

 

 

(a - b)^2   =   a^2  - 2ab  + b^2     =   ( a^2 +  b^2)  -  2ab    =  ( 4ab)   - 2ab  =  2ab

 

So

 

(a - b)^2   =  2ab         take the square root of  both sides

 

sqrt  [ (a -b)^2]   =   sqrt (2ab)

 

a  - b   =   sqrt (2ab)

 

So, subbing  into (1)

 

sqrt (2ab)              sqrt 2   * sqrt (ab)

_______  =           ______________   =      sqrt (2)

sqrt  (ab)                   sqrt (ab)

 

 

 

cool cool cool

 Feb 5, 2021

35 Online Users

avatar
avatar